Exploring meaning: an analysis of denotative diction and connotative diction in Indonesian language textbook stories for second grade elementary school - Limaran, Ken; Sukardi, Sukardi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study examines denotative and connotative diction in Indonesian textbooks for grade II primary schools under the Merdeka Curriculum. The main objective of this study is to assess how denotative and connotative word choice can affect the understanding of diction in primary school students' stories. Through the content analysis method, this study evaluated various stories in the textbook, focusing on word choice and its influence on teaching effectiveness. Denotative diction and connotative diction were chosen as the objects of analysis because of their critical role in helping students understand literal texts, which is the foundation for further learning at an early age. Increased consistency of diction use across all subject matter to support learning effectiveness at the primary level. It is hoped that these findings can be used as a reference for curriculum development and the preparation of better Indonesian language textbooks in the future, in accordance with the principles of Merdeka Curriculum which supports inclusive and comprehensive education. The conclusion of the study shows that the use of words with clear and unambiguous denotative meanings tends to make it easier for students to understand the concepts taught. Through connotative diction learners can develop analytical skills that are important in reading and understanding texts.